Suppressing dimer formation by increasing conformational freedom in multi-carbazole thermally activated delayed fluorescence emitters. Issue 1 (27th November 2020) - Salah, Lubna; Etherington, Marc K.; Shuaib, Ali; Danos, Andrew; Nazeer, Ahmed A.; Ghazal, Basma; Prlj, Antonio; Turley, Andrew T.; Mallick, Abhijit; McGonigal, Paul R.; Curchod, Basile F. E.; Monkman, Andrew P.; et al.
Abstract : Twisted carbazoles and shallow dihedral angles provide a defence against dimer formation that adversely affects OLED performance. Abstract : Ideal emitters for organic light-emitting diodes (OLEDs) are capable of efficiently harvesting non-emissive triplet states, have high colour stabilities, and possess high photoluminescence quantum yields (PLQYs). Maintaining colour stability and PLQY is particularly challenging for multi-carbazole thermally activated delayed fluorescence (TADF) materials that form persistent dimers due to intermolecular interactions of their extended aromatic systems (with altered electronic states). Addressing this challenge, three new emitters are presented, which demonstrate that, somewhat counterintuitively, sterically uncrowded acceptor units can suppress these undesirable interactions. They do so by allowing the surrounding carbazole donors to be arranged with lower dihedral angles, which in turn limits their availability for dimerization. A new pyrazine-centered emitter 4CzPyz is contrasted directly with the cyanopyridine and terephthalonitrile analogues, 4CzCNPy and 4CzTPN respectively. The pyrazine derivative demonstrates enhanced colour stability in the solid-state compared to the cyanopyridine and terephthalonitrile acceptors, which we assign to its absence of intermolecular face-to-face aromatic interactions. This suppression of dimer formation is shared by two cyanopyrazine emitters 2Cz2CNPyz and 3CzCNPyz, each of which feature reduced steric pressure and flatter Cz-Pyz dihedral angles than non-heterocyclic analogues. Flatter dihedral angles consequently lead to C–H bonds of the Cz donors extending outwards at angles that prevent the stacking required for dimerization. This expanded understanding of dimer formation in TADF materials will guide future efforts to maintain colour stability in higher performance TADF materials by curbing the prevalence of face-to-face aromatic interactions.